Treatment of Bilateral Recurrent Dislocation of Hip Prosthesis with Malpositioned Well-Fixed Shell: A Case Report - Judas, F (2013)
Dislocations of total hip prostheses cause pain and patient dissatisfaction. Recurrent dislocations are difficult to treat mainly when the acetabular metal shell is well-fixed. The purpose of this article was to describe the surgical technique used for the treatment of a bilateral recurrent posterior dislocation after a cementless total hip prosthesis, caused by ex- cessive inclination of acetabular components, in a 72-year-old patient. On both sides, acetabular metal shell, porous- coated, was well-fixed. Revision of the entire acetabular component could be an appropriate therapeutic option because it was malpositioned. Nevertheless, a conservative operation was performed. The metal shell was left in situ and the preexisting polyethylene liner was removed and replaced by a new undersized cross-linked polyethylene liner, then, cemented into the shell and properly oriented. An acetabular cemented augmentation reinforced by 3 cortical screws was associated with the reconstruction. This report suggests that cementation of new liner into a malpositioned well- fixed metal shell associated with an acetabular cemented augmentation is a simple and safe technique for the manage- ment of recurrent hip dislocation, for elderly patients in which it is advisable to avoid a major revision hip surgery by medical comorbidities. Nonetheless, further studies with medium-and long-term follow-up are needed to validate this technique.